Standardization of planting geometry for aeroponic mini-tuber production in potato (Solanum tuberosum) - SHARMA, ASHWANI K; BUCKSETH, TANUJA; SINGH, R K (The Indian Journal of Agricultural Sciences, 2020)
For optimization of potato (Solanum tuberosum L.) mini-tuber production through aeroponics, an experiment was conducted for the standardization of plant density through varying in-row and intra-row spacing’s in the aeroponic unit of ICAR-Central Potato Research Institute, Shimla, HP, India. The results revealed that the total number of mini-tubers and yield per plant obtained during all the 14 harvests were in general higher at wider intra-row spacing of 15 cm than 10cm in both the inter-row spacing’s, viz. 15 cm as well as 20 cm. On per unit area basis, the number of tubers/ m2 was maximum at the highest plant density (66 plants/m2) achieved with 15 × 10cm spacing, closely followed and at par with plant density of 44 plants/m2 (15 × 15 cm) and minimum with lowest planting density (33 plants/m2) at 20 × 15 cm. Yield/m2 was not affected significantly with the varying plant density, however, the average weight per tuber was significantly higher (1.74g) at the lowest planting density (33 plants/m2) obtained with 20 × 15cm spacing and was statistically at par among rest of the treatments.